Federal Ecosystem Management : Its Rise, Fall, and Afterlife - Skillen, James R. (Book collections on Project MUSE., 2015)
For the better part of the last century, "preservation" and "multi-use conservation" were the watchwords for managing federal lands and resources. But in the 1990s, amidst notable failures and overwhelming needs, policymakers, land managers, and environmental scholars were calling for a new paradigm: ecosystem management. Such an approach would integrate federal land and resource management across jurisdictional boundaries; it would protect biodiversity and economic development; and it would make federal management more collaborative and less hierarchical. That, at any rate, was the idea. Where the idea came from--why ecosystem management emerged as official policy in the 1990s--is half of the story that James Skillen tells in this timely book. The other half: Why, over the course of a mere decade, the policy fell out of favor? This closely focused history describes an old system of preservation and multi-use conservation ill equipped to cope with the new ecological, legal, and political realities confronting federal agencies. Ecosystem management, it was assumed, would not demand choices between substantive and procedural needs. Looming even larger in the push for the new approach was a shift of emphasis in both ecology and political science--from stability and predictability to dynamism and contingency. Ecosystem management offered more modest managerial goals informed by direct public participation as well as scientific expertise. But as Skillen shows, this purported balance proved to be the policy's undoing. Different interpretations presented conflicting emphases on scientific and democratic authority. By 2001, when both models had been tested, the Bush administration faulted federal ecosystem management for running "willy-nilly all over the west," and shelved the policy. In this book, Skillen gets at the truth behind these contrary interpretations and claims to clarify how federal ecosystem management worked--and didn't--and how many of the principles it embodied continue to influence federal land and resource management in the twenty-first century. How the policy's lessons apply to our politically and environmentally fraught moment is, finally, considerably clearer with this informed and thoughtful book in hand.--Publisher website.